Effect of High Tone Power Therapy on Cervical Proprioception and Pain in Cervical Radiculopathy Patients: A Randomized Controlled Trial (Cuestiones de Fisioterapia, 2025)
Introduction: Cervical radiculopathy (CR), is a major disorder that could affect individual function due to the irritation of the nerve roots causing pain, disability, and decreasing neck proprioceptive function, thus this study aims to investigate the impact of High Tone Power Therapy (HTT) on neck pain and proprioception in cervical radiculopathy. Material andmethods: Forty two patients underwent pre- and post-treatment evaluations. The cervical joint position sense error (JPSE) test using the laser pointer, the neck disability index (NDI), the cervical range of motion (CROM) goniometer device measurements, and the visual analogue scale for pain (VAS-P) were among the outcome measures. The control group received the selected physical therapy program and sham High Tone Power Therapy without current flow, while the study group received High Tone Power Therapy and the selected physical therapy program. Both groups had three sessions per week for four weeks. Results: Following treatment, the results showed a considerable improvement, with the study group’s cervical range of motion scores increasing more than the control group's and the neck cervical joint position sense error, neck disability index, and VAS-P significantly declining (p < 0.05). Conclusions: An efficient physical therapy intervention for enhancing neck proprioception and reducing the symptoms of cervical radiculopathy should include High Tone Power Therapy.